2022
DOI: 10.3389/fgene.2022.807381
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Data Analysis and a Case-Control Study in Mexican Population Reveals Lipid Trait Associations of New and Known Genetic Variants in Dyslipidemia-Associated Loci

Abstract: Background: Plasma lipid levels are a major risk factor for cardiovascular diseases. Although international efforts have identified a group of loci associated with the risk of dyslipidemia, Latin American populations have been underrepresented in these studies.Objective: To know the genetic variation occurring in lipid-related loci in the Mexican population and its association with dyslipidemia.Methods: We searched for single-nucleotide variants in 177 lipid candidate genes using previously published exome seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Several studies confirm a variety of loci, not always in LD, mapping on the APOC1, APOC3, and APOA5 clusters and its relation to blood lipids [38][39][40]. Variant APOC3 rs147210663 has been reported over 40 times associated to dyslipidemia, cholesterol, and BMI, it is in LD with APOC3 rs5128 here identified, and whose association with triglyceride levels in Pima Amerindians has been reported as a founder mutation [41]. Also, a recent multi-ancestry analysis on 170,000 exomes including 16,440 individuals of "Hispanic" origin reported that APOC3 is a relevant gene for HDL-C and the TG/HDL-C ratio [11].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Several studies confirm a variety of loci, not always in LD, mapping on the APOC1, APOC3, and APOA5 clusters and its relation to blood lipids [38][39][40]. Variant APOC3 rs147210663 has been reported over 40 times associated to dyslipidemia, cholesterol, and BMI, it is in LD with APOC3 rs5128 here identified, and whose association with triglyceride levels in Pima Amerindians has been reported as a founder mutation [41]. Also, a recent multi-ancestry analysis on 170,000 exomes including 16,440 individuals of "Hispanic" origin reported that APOC3 is a relevant gene for HDL-C and the TG/HDL-C ratio [11].…”
Section: Discussionmentioning
confidence: 75%
“…Also, a recent multi-ancestry analysis on 170,000 exomes including 16,440 individuals of "Hispanic" origin reported that APOC3 is a relevant gene for HDL-C and the TG/HDL-C ratio [11]. To further delve into the relevance of the APOC3 and chromosome 11 loci, Jurado-Camacho et al described the APOA1/C3/A5-ZPR1-BUD13 cluster and its impact on several lipid traits including, HDL-C and TG [41]. These observations agree with our results of the intron variant APOC3 rs5128 as significantly associated to the AIP index in Mexican adults highlighting that the connection of APOC3 and blood triglycerides is likely population independent [42].…”
Section: Discussionmentioning
confidence: 99%
“…Variant APOC3 rs147210663 has been reported to be associated with dyslipidemia, cholesterol, and BMI over 40 times. It is in LD with APOC3 rs5128 identified here, and its association with triglycerides in Pima Amerindians has been reported as a founder mutation [ 28 ]. Additionally, a recent multi-ancestry analysis on 170,000 exomes, including 16,440 individuals of “Hispanic” origin, reported that APOC3 is a relevant gene for HDL-C and the TG/HDL-C ratio [ 11 ].…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, a recent multi-ancestry analysis on 170,000 exomes, including 16,440 individuals of “Hispanic” origin, reported that APOC3 is a relevant gene for HDL-C and the TG/HDL-C ratio [ 11 ]. To further delve into the relevance of the APOC3 and chromosome 11 loci, Jurado-Camacho et al described the APOA1/C3/A5-ZPR1-BUD13 cluster and its impact on several lipid traits, including HDL-C and TG [ 28 ]. These observations agree with our results of the intron variant APOC3 rs5128 as significantly associated with the AIP index in Mexican adults, highlighting that the connection of APOC3 and blood triglycerides is likely population independent [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation